Optimalizace supermarketu na projektu G463 - Tollingerová, Nikola; Tollingerová Nikola (České vysoké učení technické v Praze, 2019)
Diplomová práce se zabývá návrhem nového uspořádání supermarketu. V úvodní části diplomové práce je popsán automobilový průmysl v České republice, ve světě a jeho nejvýznamnější charakteristiky. Další kapitoly obsahují popis firmy, ve které se supermarket nachází. Druhá část je zaměřena na návrh supermarketu a snížení celkových zásob. Poslední kapitola obsahuje porovnání nákladů a úspor.

Diploma thesis deals with the design of a new supermarket arrangement. The introductory part of the diploma thesis describes the automotive industry in the Czech Republic, the world and its most important characteristics. Other chapters contain a description of the company, in which the supermarket is located. The second part focuses on designing a supermarket and reducing overall inventory. The last chapter contains a comparison of costs and savings.
Optimalization of the Supermarket for Project G463
Keywords: Supermarket,automobilový průmysl,zásoby; Supermarket,automotive,stock